Síntese e Espectroscopia Óptica das fases estáveis do sistema Y2O3-Al2O3 dopadas com Nd3+ e Sm3+ - Silva, Tarcio de Castro (2013)
The development of rare earths luminescent materials has been subject of many research works searching for technological applications in the manufacture of solid-state lasers, photonic and biomedical devices, manufacturing of displays, and others. The system Y2O3-Al2O3 has three stable crystalline phases: Y3Al5O12 (YAG), YAlO3 (YAP) and Y4Al2O9 (YAM). Among them, YAP and YAG are widely studied and used in the manufacture of solid-state lasers. In this work, we used the modified polymeric precursor method to synthesize YAG, YAP, and YAM doped with 0.5 and 1% of Nd3+ and Sm3+ ions replacing Y3+. Analysis of X ray diffraction and vibrational spectroscopy confirmed the achievement of crystalline single phases. Transmission electron images show grain sizes ranging from 80 to 300 nm. We verified a strong influence of the different matrices symmetries on the optical emission of these rare earths photoluminescent ions.